2015
DOI: 10.2174/138161282131151013191051
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplatforms for Delivery of siRNA to the Eye

Abstract: Drug delivery to the eye is challenging for formulation scientists due to physiological barriers that separate the eye from the rest of the body. A variety of ocular disorders demand the development of optimal drug delivery systems for the administration of drugs and therapeutic agents that can overcome barriers that restrict drug bioavailability. SiRNA inhibits the expression of target genes and has immense potential as a biological tool for the therapeutic inhibition of disease causing genes; however, delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Remarkably, in contrast to numerous examples of successful delivery of therapeutic agents to ocular tissues with nanocarrier systems, the development of polymeric nanomicelles for back of the eye delivery has rarely been addressed. However, such a nanomicellar approach may be desirable, for instance, in case of a drug such as cidofovir, which has lower bioavailability in human ocular tissues following intravenous or intravitreal administration. , …”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, in contrast to numerous examples of successful delivery of therapeutic agents to ocular tissues with nanocarrier systems, the development of polymeric nanomicelles for back of the eye delivery has rarely been addressed. However, such a nanomicellar approach may be desirable, for instance, in case of a drug such as cidofovir, which has lower bioavailability in human ocular tissues following intravenous or intravitreal administration. , …”
Section: Introductionmentioning
confidence: 99%
“…The major obstacles for the drug treatments are the presence of a restrictive blood-retina barrier (BRB), which limits the drug entry into ocular tissues and results in undesired irreversible neuronal damage. Recent advances in nanotechnology have revealed that novel nano-platforms are greatly promising in enhancing drug delivery while being intrusive less to the eye systems (Leon et al, 2000;De Jong & Borm, 2008;Kataki et al, 2015). The nanoscale drug-loading system in ophthalmic medication enables effective drug delivery as it can penetrate the BRB and hence, overcome the aforementioned challenges in the ocular disorder therapeutics (Kataki et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in nanotechnology have revealed that novel nano-platforms are greatly promising in enhancing drug delivery while being intrusive less to the eye systems (Leon et al, 2000;De Jong & Borm, 2008;Kataki et al, 2015). The nanoscale drug-loading system in ophthalmic medication enables effective drug delivery as it can penetrate the BRB and hence, overcome the aforementioned challenges in the ocular disorder therapeutics (Kataki et al, 2015). It also improves the bioavailability of drugs significantly, reduces the dosage as well as usage frequency of drugs, and enhances the safety and longevity of the drug (De Jong & Borm, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, transfection of cells is currently more efficacious via AAV-vectors than via nanoparticles, but researchers are confident that the easy and diverse modification options of nanoparticles can remedy this deficit in the near future. Instead of carrying plasmid DNA, nanoparticles can likewise carry siRNA to silence specific genes by RNA interference [62]. This method is well suited for the treatment of acute diseases.…”
Section: Gene or Sirna Delivery To The Eye Via Nanotechnologymentioning
confidence: 99%